KONSEP DASAR PENDIDIKAN BERBASIS MASYARAKAT - Toto Suharto (LPMPP Universitas Negeri Yogyakarta, 2005)
AbstractDemocratization of education can be actualized through, among others, the application of the concept of community-based education. This article is philosophically aimed at exploring the basic ideas and concepts implied in community-based education. What is community-based education? Why does the concept need to be implemented in educational management? The problem of community-based education is a new subject of discourse appearing in the educational world and especially in Indonesian society.Community-based education is a system of education in which the community makes a high proportion of decisions concerning education, starting from matters of the input, process, and output through to the financing of education. The concept of community-based education appears urgent to be implemented for the sake of democratization of education. Community-based education represents a political struggle for social transformation. Thus, community-based education is part of an agenda of critical pedagogy which attempts to liberate education from the shackles of political power. When education has been libera-ted from the domination and hegemony of such power, it means that democratization of education has been actualized.Key words: democratization of education, community-based education,critical pedagogy